Assessment of Resting Heart Rate and Body Composition among Exercise Performers: Resting Heart Rate and Body Composition - Nawaz, Fozia; Khan, Alamgir; Zafar Iqbal, Muhammad; Bhatti , Shireen; Jamil, Muhammad; Selamoglu, Zeliha; Khan, Samiullah; Aslam, Soniha; Ali Soomro, Javed (Pakistan BioMedical Journal, 2022)
Obesity is a global health issue and millions of people around the globe have obesity. Objective: To examine the effect of aerobic exercise on resting heart rate and various parameters of body composition. Methods: It was a randomized controlled trial. The participants of the study included forty (40) volunteer inter collegiate females of Punjab Pakistan. They were randomly categorized into two groups i.e. control group (CG) and experimental group (EG). It was conducted by following the prescribed exercise protocols of eight (08) weeks. A written informed consent was taken from each subject before participation in the study. After completion of the exercise protocols, the pre and post test data were processed through statistical package for social sciences (SPSS, version,25) Results: The RHR of the 40 participants in pretest was (76.37± 5.63) and in posttest was (73.55± 5.51). The HRR of the 40 participants in pretest was (116.70± 4.46) and in posttest was (110.77± 10.00). In respect of resting heart score of EGs in pretest and posttest the data indicate that the score of pretest of RHR (76.35± 3.85) and post of RHR (71.55± 3.45) were significantly different. In respect of resting heart score of control group in pretest and posttest the data indicate that the score of pretest of RHR (76.40± 7.09) and post of RHR (75.55± 6.48) were not significantly different. In the same way, significantly the pretest measurement of HRR (117.30± 5.74), of control group was not different from the posttest measurement of HRR (119.51± 4.65) t19= -1.714, p≤ 0.05. However, the researcher concluded that before the treatment the EG and CG were balanced in body composition, RHR and HRR. Hence the researcher found that there is significant difference between EG and CG in body composition, RHR and HRR after the treatment.Conclusion: Based on analysis, the researcher concluded that aerobic exercise has significant impact on resting heart rate and various parameters of body composition among female exercise performers.